Dynamic model and control for 3DOF agricultural robot - Omrane, Bouketir; Wan Ismail, Wan Ishak; Mahmud, Hilmi; Bardaie, Mohd Zohadi (Universiti Putra Malaysia, 1999)
To endow great capabilities to an agricultural robot for harvesting operations to identify the fruits, a CCD camera mounted on its end-effector and an interfacing system for controlling the process was developed. This paper will discuss on a dynamic model of a 3DOF agricultural robot and control strategy that was used and on the hardware interfacing. The dynamic model is the mathematical formulations of the equations of the robot arm motion. The control strategy depends on the kinematics and dynamic derivation. The purpose of robot arm control is to maintain the dynamic response of the manipulator in accordance with some pre-specified performance criteria. Since hydraulic power is used to actuate the whole arm, the control method is based on the control of the length of linear actuators and of the revolution of the shaft of the rotary actuator according to the position of the end-effector to control the joint angles.